Optimal Peer-to-Peer Energy Sharing Between Prosumers Using Hydrokinetic, Diesel Generator and Pumped Hydro Storage - Kusakana, Kanzumba (Journal of Energy Storage, 2019)
In this paper, an optimal Peer-to-Peer energy sharing model between two small prosumers is developed and simulated in the south African context. For this purpose, a case study of a commercial type prosumer sharing power with a residential prosumer, both on the same premise, is used to demonstrate the effectiveness of the model. The commercial prosumer owns a small hydrokinetic system operating in conjunction with a pumped hydro storage while the residential prosumer has a diesel generator. The developed model aims to minimize the resulting cost of energy linked to the diesel generator, while optimizing the power flow between the two prosumers. Using actual data, the developed model has been used to simulate and analyze the complex interaction between the different power sources, the energy storage and the demands within the proposed system sizing and operation constraints. The simulation results show that the power flows can be optimally managed, resulting in a substantial reduction in the residential prosumer's operation cost which can now rely not only on its diesel generator but also on the power shared by the hydrokinetic and pumped hydro system of the commercial prosumer.
Published Article
Keywords: Consumer; Diesel Generator; Hydrokinetic; Peer-to-Peer Energy Sharing; Pumped Hydro Storage; Prosumers, South Africa